Explicitly accounting for needle sugar pool size crucial for predicting intra-seasonal dynamics of needle carbohydrates δ18O and δ13C - Leppä, Kersti; Tang, Yu; Ogée, Jérôme; Launiainen, Samuli; Kahmen, Ansgar; Kolari, Pasi; Sahlstedt, Elina; Saurer, Matthias; Schiestl‐Aalto, Pauliina; Rinne‐Garmston, Katja T. (Wiley, 2022)
Summary We explore needle sugar isotopic compositions (δ18O and δ13C) in boreal Scots pine (Pinus sylvestris) over two growing seasons. A leaf-level dynamic model driven by environmental conditions and based on current understanding of isotope fractionation processes was built to predict δ18O and δ13C of two hierarchical needle carbohydrate pools, accounting for the needle sugar pool size and the presence of an invariant pinitol pool. Model results agreed well with observed needle water δ18O, δ18O and δ13C of needle water-soluble carbohydrates (sugars + pinitol), and needle sugar δ13C (R2 = 0.95, 0.84, 0.60, 0.73, respectively). Relative humidity (RH) and intercellular to ambient CO2 concentration ratio (Ci/Ca) were the dominant drivers of δ18O and δ13C variability, respectively. However, the variability of needle sugar δ18O and δ13C was reduced on diel and intra-seasonal timescales, compared to predictions based on instantaneous RH and Ci/Ca, due to the large needle sugar pool, which caused the signal formation period to vary seasonally from 2 d to more than 5 d. Furthermore, accounting for a temperature-sensitive biochemical 18O-fractionation factor and mesophyll resistance in 13C-discrimination were critical. Interpreting leaf-level isotopic signals requires understanding on time integration caused by mixing in the needle sugar pool.
Keywords: boreal forest; carbon isotope; dynamic modeling; needle sugar; oxygen isotope; photosynthesis; Scots pine (Pinussylvestris)